Proceedings of the Fifth Euro-China Conference on Intelligent Data Analysis and Applications - Krömer, Pavel; Zhang, Hong; Liang, Yongquan; Pan, Jeng-Shyang (Advances in Intelligent Systems and Computing,, 2019)
This volume of Advances in Intelligent Systems and Computing highlights papers presented at the Fifth Euro-China Conference on Intelligent Data Analysis and Applications (ECC2018), held in Xi'an, China from October 12 to 14 2018. The conference was co-sponsored by Springer, Xi'an University of Posts and Telecommunications, VSB Technical University of Ostrava (Czech Republic), Fujian University of Technology, Fujian Provincial Key Laboratory of Digital Equipment, Fujian Provincial Key Lab of Big Data Mining and Applications, and Shandong University of Science and Technology in China. The conference was intended as an international forum for researchers and professionals engaged in all areas of computational intelligence, intelligent control, intelligent data analysis, pattern recognition, intelligent information processing, and applications.